Design method of low-polymer low-strength concrete

By selecting appropriate materials and carrying out screening processing in the design of oligomer low-strength concrete, the problems of high cost and inconsistent strength of waste concrete block crushing are solved, and the stability and economical improvement of concrete performance are achieved.

CN119361039APending Publication Date: 2025-01-24THE THIRD CONSTR OF CHINA CONSTR EIGHTH ENG BUREAU
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411388844.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing oligomer low-strength concrete design requires crushing treatment when using discarded concrete blocks, resulting in high treatment costs and inconsistent concrete strength, affecting the performance of new concrete.

Method used

Adopt the oligomer low-strength concrete design method, select suitable curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials, and make the iron tailings particle size uniform through screening treatment, and design a reasonable Material proportions, tests and adjustments are made to ensure that the concrete performance meets the design requirements.

Benefits of technology

It reduces the problem of increasing costs caused by the complexity of waste concrete block treatment, which improves the consistency and stability of concrete performance, reduces carbon emissions, and saves materials and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361039A_ABST
    Figure CN119361039A_ABST
Patent Text Reader

Abstract

The invention discloses a design method of low-polymer low-strength concrete. The design method comprises the following steps: S1, determining design requirements: determining the requirements of the strength grade, the use environment and the working performance of the concrete; s2, selecting materials: selecting proper curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials; s3, designing a mix proportion: designing the proportion of a curing agent, coarse aggregate, iron tailings, water, a water reducing agent and an early strength agent material according to the strength requirement and the working performance of the concrete; and S4, testing and adjusting: carrying out a concrete trial preparation test, and optimizing the mix proportion according to detection data and a standard method. According to the low-polymer low-strength concrete design method, proper curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials are selected, and the iron tailings are screened, so that the overall granularity is relatively uniform, the problem of inconsistent strength caused by use of waste concrete blocks is reduced, and the utilization rate of the iron tailings is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of industrial waste recycling, in particular to a design method for oligomer low-strength concrete. Background Art

[0002] Concrete is widely used in roads, bridges and various buildings due to its advantages such as high strength and convenient construction. However, the existing low-strength oligomer concrete design still has certain defects, such as;

[0003] During the use process, a large amount of industrial waste is accumulated in society, and the overall utilization rate is low, which brings a certain burden to the ecological environment;

[0004] In order to overcome the above defects, prior art 1 (Chinese patent with application number 201911393842.7 and application date 2019-12-30) is a concrete processing process doped with waste concrete blocks, and the specific steps are divided into pretreatment of waste concrete blocks, decomposition treatment of the surface of concrete fine blocks, preparation of coarse aggregate, and preparation process of cementitious materials. The waste concrete blocks are recycled and reused, and concrete fine blocks are obtained after crushing and fine crushing. After surface modification, a strong acid salt layer is formed on the surface of the concrete fine blocks, and after being mixed with fine sand and blast furnace slag in a reasonable ratio, a strong acid salt layer is formed on the surface of the concrete fine blocks. Forming coarse aggregate; Recycling and reusing waste rubber particles, adding rubber to concrete can solve the brittleness problem of concrete, and the concrete has the advantages of light weight, elastic shock absorption, noise reduction and sound insulation, air permeability and water permeability, good ductility and toughness, and forms a cementitious material with cement and fly ash in a reasonable proportion; This concrete processing technology improves the microscopic uniformity of the concrete interface, and the multi-step mixing process reduces the agglomeration of cement particles, improves the dispersibility of cement particles, and increases the degree of hydration. At the same time, it improves the distribution state of hydration products in the concrete interface area, and comprehensively improves various properties of concrete;

[0005] There is also prior art 2 (Chinese patent with application number 202110433134.2 and application date 2021-04-22), a method for preparing recycled concrete doped with waste concrete blocks, step 1, raw material processing: crushing and cleaning the waste concrete blocks to obtain recycled aggregates; step 2, mixing and stirring: adding cement to the recycled aggregates prepared in step 1, stirring evenly to obtain mixed dry materials; step 3, adding water and stirring: adding water to the mixed dry materials prepared in step 2, stirring to obtain recycled concrete;

[0006] And prior art 3 (Chinese patent with application number 202011440620.9 and application date 2020-12-07) a concrete processing process doped with waste concrete blocks and recycled concrete prepared therefrom, S1 pretreatment: take waste concrete blocks and crush them into old concrete particles; take seaweed fiber, add aminopropyltriethoxysilane and nano-Beta molecular sieve, mix evenly, add water, stir, add old concrete particles, stir evenly, dry, and obtain recycled aggregate; S2 premixing: take premixed raw materials, add recycled aggregate, mix evenly, and obtain powder; the premixed raw materials include coarse aggregate, fine aggregate and fly ash; S3 concrete preparation: take water, add additives, stir, then add powder, then add cement, continue stirring, and obtain recycled concrete; the additives include water reducers.

[0007] Although the existing technology can be used to recycle industrial waste, the waste concrete blocks need to be crushed and processed during the working process, which increases the overall processing cost. In addition, since a large number of microcracks will be generated inside the waste concrete blocks when they are crushed, it is easy to cause a decrease in the subsequent bonding strength. The cracked concrete blocks will increase their water absorption capacity, which will reduce the performance of the new concrete. In addition, the direct use of the waste concrete blocks will lead to inconsistent concrete strength, thereby affecting the performance of the new concrete.

[0008] In response to the above problems, it is urgently necessary to carry out innovative design based on the original oligomer low-strength concrete design method. Therefore, we proposed a oligomer low-strength concrete design method that can well solve the above problems. Summary of the invention

[0009] The purpose of the present invention is to provide a method for designing low-strength oligomer concrete to solve the problem that the waste concrete blocks in the current market need to be crushed and processed as mentioned in the above background technology, which increases the overall processing cost. In addition, a large number of microcracks will be generated inside the waste concrete blocks when they are crushed, which will easily lead to a decrease in the subsequent bonding strength. The water absorption capacity of the cracked concrete blocks will increase, which will reduce the performance of the new concrete. In addition, the direct use of the waste concrete blocks will lead to inconsistent concrete strength, thereby affecting the performance of the new concrete.

[0010] To achieve the above object, the present invention provides the following technical solution: a method for designing oligomer low-strength concrete, comprising the following steps:

[0011] S1: Determine the design requirements: clarify the strength grade of concrete, the use environment and the requirements for working performance;

[0012] S2: Select materials: Select suitable curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials;

[0013] S3: Mix design: Design the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent according to the concrete strength requirements and working performance;

[0014] S4: Testing and adjustment: Conduct concrete trial mix tests and optimize the mix ratio based on test data and standard methods;

[0015] S5: Construction plan: formulate construction methods, including specific measures for mixing, transportation, pouring, vibration and maintenance;

[0016] S6: Quality control: Perform quality control during the construction process to ensure that the performance of the concrete meets the design requirements;

[0017] S7: Maintenance and evaluation: Proper maintenance should be carried out after concrete pouring, and the strength and performance of concrete should be evaluated regularly to ensure long-term stability, effectively reduce carbon emissions, save materials and reduce production costs overall.

[0018] Preferably, the curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials are mixed according to proportion.

[0019] Preferably, the mass of the curing agent accounts for 1 of the total amount of concrete, the mass of the coarse aggregate accounts for 2.2-3.6 of the total amount of concrete, and the mass of the iron tailings accounts for 0.8-2.0 of the total amount of concrete.

[0020] Preferably, the mass of water accounts for 0.92 of the total amount of concrete, the mass of the water reducing agent accounts for 0.01-0.015 of the total amount of concrete, and the mass of the early strength agent accounts for 0.015 of the total amount of concrete.

[0021] Preferably, the concrete trial mix test observes and records the compressive strength and slump of the concrete at three days, seven days and twenty-eight days respectively.

[0022] Preferably, after the concrete trial mix test, the fluidity, compressive strength, flexural strength and vertical expansion of the concrete are tested, and the mix ratio is optimized based on the test data and standard methods so that the overall test data meets the measurement standards.

[0023] Preferably, a composite concrete material with good working performance is prepared through the synergistic effect of the material and steel slag.

[0024] Compared with the prior art, the invention has the following beneficial effects: the method for designing low-strength oligomer concrete selects suitable curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials, and the iron tailings are screened to make the overall particle size more uniform, which not only reduces the problem of inconsistent strength caused by the use of waste concrete blocks, but also improves the utilization rate of iron tailings. The specific contents are as follows:

[0025] (1) After screening, the iron tailings have a more uniform particle size, which can provide more consistent concrete performance. This not only reduces the problem of inconsistent strength caused by the use of waste concrete blocks, but also improves the utilization rate of iron tailings;

[0026] (2) Designing the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent based on the concrete strength requirements and workability, and mixing the above materials so that the physical and chemical properties of concrete can be optimized through processing and control;

[0027] (3) By testing the fluidity, compressive strength, flexural strength and vertical expansion of concrete and optimizing the mix ratio based on the test data and standard methods, the overall test data meets the measurement standards, reducing the problem of performance being affected by the use of discarded concrete blocks; BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the first group of contents of the present invention;

[0029] Figure 2 This is the first group of content bar graphs of the present invention;

[0030] Figure 3 This is a schematic diagram of the second group of contents of the present invention;

[0031] Figure 4 This is a schematic diagram of the second group of contents of the present invention;

[0032] Figure 5 This is a schematic diagram of the third group of contents of the present invention;

[0033] Figure 6 This is the third group of content bar graphs of the present invention;

[0034] Figure 7 This is a schematic diagram of the fourth group of contents of the present invention;

[0035] Figure 8 This is the fourth group of content bar graphs of the present invention;

[0036] Fig. 9 This is a schematic diagram of the fifth group of contents of the present invention;

[0037] Fig.10 This is the fifth group of content bar graphs of the present invention;

[0038] Fig.11 It is a schematic diagram of the test results of the present invention. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Embodiment 1:

[0041] S1: Determine the design requirements: clarify the strength grade of concrete, the use environment and the requirements for working performance;

[0042] S2: Material selection: Select appropriate curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent. The iron tailings are screened to make the overall particle size more uniform, which can provide more consistent concrete performance. It not only reduces the problem of inconsistent strength caused by the use of waste concrete blocks, but also improves the utilization rate of iron tailings;

[0043] S3: Mix design: Design the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent according to the concrete strength requirements and working performance;

[0044] Among them, the mass of the curing agent accounts for 1 of the total amount of concrete, the mass of the coarse aggregate accounts for 2.88 of the total amount of concrete, the mass of the iron tailings accounts for 0.86 of the total amount of concrete, the mass of the water accounts for 0.92 of the total amount of concrete, the mass of the water reducer accounts for 0.01 of the total amount of concrete, and the mass of the early strength agent accounts for 0.015 of the total amount of concrete. By mixing the above materials, the physical and chemical properties of the concrete can be optimized through treatment and control, reducing the problem of increased costs caused by the complicated treatment process of waste concrete blocks;

[0045] S4: Test and adjustment: Conduct concrete trial mix test, observe the compressive strength and slump of concrete at three, seven and twenty-eight days respectively. The ability of concrete material with this mix ratio to resist damage under external force is 15.85Mpa at three days, 20.53Mpa at seven days and 23.31Mpa at twenty-eight days, and its slump is 160mm;

[0046] The fluidity, compressive strength, flexural strength and vertical expansion of concrete were tested, and the mix ratio was optimized according to the test data and standard methods. The initial test value of concrete fluidity was 374, 277 after 30 minutes, the compressive strength was 35.7Mpa after 12 hours, 70.6Mpa after 3 days, and 123.5Mpa after 28 days. The overall bending strength was 6.8Mpa after 3 days, and the difference between the overall vertical expansion rate of 24 hours and 3 hours was 0.11. The overall test data met the measurement standards, reducing the problem of performance being affected by the use of discarded concrete blocks;

[0047] S5: Construction plan: formulate construction methods, including specific measures for mixing, transportation, pouring, vibration and maintenance;

[0048] S6: Quality control: Perform quality control during the construction process to ensure that the performance of the concrete meets the design requirements;

[0049] S7: Maintenance and evaluation: Proper maintenance should be carried out after concrete pouring, and the strength and performance of concrete should be evaluated regularly to ensure long-term stability, effectively reduce carbon emissions, save materials and reduce production costs overall.

[0050] Embodiment 2:

[0051] S1: Determine the design requirements: clarify the strength grade of concrete, the use environment and the requirements for working performance;

[0052] S2: Material selection: Select appropriate curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent. The iron tailings are screened to make the overall particle size more uniform, which can provide more consistent concrete performance. It not only reduces the problem of inconsistent strength caused by the use of waste concrete blocks, but also improves the utilization rate of iron tailings;

[0053] S3: Mix design: Design the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent according to the concrete strength requirements and working performance;

[0054] Among them, the mass of the curing agent accounts for 1 of the total amount of concrete, the mass of the coarse aggregate accounts for 2.32 of the total amount of concrete, the mass of the iron tailings accounts for 0.9 of the total amount of concrete, the mass of the water accounts for 0.92 of the total amount of concrete, the mass of the water reducer accounts for 0.012 of the total amount of concrete, and the mass of the early strength agent accounts for 0.015 of the total amount of concrete. By mixing the above materials, the physical and chemical properties of the concrete can be optimized through treatment and control, reducing the problem of increased costs caused by the complicated treatment process of waste concrete blocks;

[0055] S4: Test and adjustment: Conduct concrete trial mix test, observe the compressive strength and slump of concrete at three, seven and twenty-eight days respectively. The ability of concrete material under this mix ratio to resist damage under external force is 16.01Mpa at three days, 21.35Mpa at seven days and 25.48Mpa at twenty-eight days, and its slump is 160mm;

[0056] The fluidity, compressive strength, flexural strength and vertical expansion of concrete were tested, and the mix ratio was optimized according to the test data and standard methods. The initial test value of concrete fluidity was 374, 277 after 30 minutes, the compressive strength was 35.7Mpa after 12 hours, 70.6Mpa after 3 days, and 123.5Mpa after 28 days. The overall bending strength was 6.8Mpa after 3 days, and the difference between the overall vertical expansion rate of 24 hours and 3 hours was 0.11. The overall test data met the measurement standards, reducing the problem of performance being affected by the use of discarded concrete blocks;

[0057] S5: Construction plan: formulate construction methods, including specific measures for mixing, transportation, pouring, vibration and maintenance;

[0058] S6: Quality control: Perform quality control during the construction process to ensure that the performance of the concrete meets the design requirements;

[0059] S7: Maintenance and evaluation: Proper maintenance should be carried out after concrete pouring, and the strength and performance of concrete should be evaluated regularly to ensure long-term stability, effectively reduce carbon emissions, save materials and reduce production costs overall.

[0060] Embodiment three:

[0061] S1: Determine the design requirements: clarify the strength grade of concrete, the use environment and the requirements for working performance;

[0062] S2: Material selection: Select appropriate curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent. The iron tailings are screened to make the overall particle size more uniform, which can provide more consistent concrete performance. It not only reduces the problem of inconsistent strength caused by the use of waste concrete blocks, but also improves the utilization rate of iron tailings;

[0063] S3: Mix design: Design the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent according to the concrete strength requirements and working performance;

[0064] Among them, the mass of the curing agent accounts for 1 of the total amount of concrete, the mass of the coarse aggregate accounts for 2.88 of the total amount of concrete, the mass of the iron tailings accounts for 0.86 of the total amount of concrete, the mass of the water accounts for 0.92 of the total amount of concrete, the mass of the water reducer accounts for 0.01 of the total amount of concrete, and the mass of the early strength agent accounts for 0.015 of the total amount of concrete. By mixing the above materials, the physical and chemical properties of the concrete can be optimized through treatment and control, reducing the problem of increased costs caused by the complicated treatment process of waste concrete blocks;

[0065] S4: Test and adjustment: Conduct concrete trial mix tests, and observe the compressive strength and slump of concrete at three, seven and twenty-eight days. The concrete material with this mix ratio has the ability to resist damage under external forces of 12.67Mpa at three days, 14.26Mpa at seven days and 21.42Mpa at twenty-eight days, and its slump is 160mm;

[0066] The fluidity, compressive strength, flexural strength and vertical expansion of concrete were tested, and the mix ratio was optimized according to the test data and standard methods. The initial test value of concrete fluidity was 374, 277 after 30 minutes, the compressive strength was 35.7Mpa after 12 hours, 70.6Mpa after 3 days, and 123.5Mpa after 28 days. The overall bending strength was 6.8Mpa after 3 days, and the difference between the overall vertical expansion rate of 24 hours and 3 hours was 0.11. The overall test data met the measurement standards, reducing the problem of performance being affected by the use of discarded concrete blocks;

[0067] S5: Construction plan: formulate construction methods, including specific measures for mixing, transportation, pouring, vibration and maintenance;

[0068] S6: Quality control: Perform quality control during the construction process to ensure that the performance of the concrete meets the design requirements;

[0069] S7: Maintenance and evaluation: Proper maintenance should be carried out after concrete pouring, and the strength and performance of concrete should be evaluated regularly to ensure long-term stability, effectively reduce carbon emissions, save materials and reduce production costs overall.

[0070] Embodiment 4:

[0071] S1: Determine the design requirements: clarify the strength grade of concrete, the use environment and the requirements for working performance;

[0072] S2: Material selection: Select appropriate curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent. The iron tailings are screened to make the overall particle size more uniform, which can provide more consistent concrete performance. It not only reduces the problem of inconsistent strength caused by the use of waste concrete blocks, but also improves the utilization rate of iron tailings;

[0073] S3: Mix design: Design the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent according to the concrete strength requirements and working performance;

[0074] Among them, the mass of the curing agent accounts for 1 of the total amount of concrete, the mass of the coarse aggregate accounts for 2.32 of the total amount of concrete, the mass of the iron tailings accounts for 0.91 of the total amount of concrete, the mass of the water accounts for 0.92 of the total amount of concrete, the mass of the water reducer accounts for 0.012 of the total amount of concrete, and the mass of the early strength agent accounts for 0.015 of the total amount of concrete. By mixing the above materials, the physical and chemical properties of the concrete can be optimized through treatment and control, reducing the problem of increased costs caused by the complicated treatment process of waste concrete blocks;

[0075] S4: Test and adjustment: Conduct concrete trial mix test, observe the compressive strength and slump of concrete at three, seven and twenty-eight days respectively. The ability of concrete material under this mix ratio to resist damage under external force is 13.07Mpa at three days, 15.55Mpa at seven days and 22.15Mpa at twenty-eight days, and its slump is 160mm;

[0076] The fluidity, compressive strength, flexural strength and vertical expansion of concrete were tested, and the mix ratio was optimized according to the test data and standard methods. The initial test value of concrete fluidity was 374, 277 after 30 minutes, the compressive strength was 35.7Mpa after 12 hours, 70.6Mpa after 3 days, and 123.5Mpa after 28 days. The overall bending strength was 6.8Mpa after 3 days, and the difference between the overall vertical expansion rate of 24 hours and 3 hours was 0.11. The overall test data met the measurement standards, reducing the problem of performance being affected by the use of discarded concrete blocks;

[0077] S5: Construction plan: formulate construction methods, including specific measures for mixing, transportation, pouring, vibration and maintenance;

[0078] S6: Quality control: Perform quality control during the construction process to ensure that the performance of the concrete meets the design requirements;

[0079] S7: Maintenance and evaluation: Proper maintenance should be carried out after concrete pouring, and the strength and performance of concrete should be evaluated regularly to ensure long-term stability, effectively reduce carbon emissions, save materials and reduce production costs overall.

[0080] Embodiment five:

[0081] S1: Determine the design requirements: clarify the strength grade of concrete, the use environment and the requirements for working performance;

[0082] S2: Material selection: Select appropriate curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent. The iron tailings are screened to make the overall particle size more uniform, which can provide more consistent concrete performance. It not only reduces the problem of inconsistent strength caused by the use of waste concrete blocks, but also improves the utilization rate of iron tailings;

[0083] S3: Mix design: Design the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent according to the concrete strength requirements and working performance;

[0084] Among them, the mass of the curing agent accounts for 1 of the total amount of concrete, the mass of the coarse aggregate accounts for 3.48 of the total amount of concrete, the mass of the iron tailings accounts for 1.87 of the total amount of concrete, the mass of the water accounts for 0.92 of the total amount of concrete, the mass of the water reducing agent accounts for 0.01 of the total amount of concrete, and the mass of the early strength agent accounts for 0.015 of the total amount of concrete. By mixing the above materials, the physical and chemical properties of the concrete can be optimized through treatment and control, reducing the problem of increased costs caused by the complicated treatment process of waste concrete blocks;

[0085] S4: Test and adjustment: Conduct concrete trial mix tests, and observe the compressive strength and slump of concrete at three, seven and twenty-eight days. The concrete material with this mix ratio has the ability to resist damage under external forces of 11.75Mpa at three days, 15.28Mpa at seven days and 21.42Mpa at twenty-eight days, and its slump is 160mm;

[0086] The fluidity, compressive strength, flexural strength and vertical expansion of concrete were tested, and the mix ratio was optimized according to the test data and standard methods. The initial test value of concrete fluidity was 374, 277 after 30 minutes, the compressive strength was 35.7Mpa after 12 hours, 70.6Mpa after 3 days, and 123.5Mpa after 28 days. The overall bending strength was 6.8Mpa after 3 days, and the difference between the overall vertical expansion rate of 24 hours and 3 hours was 0.11. The overall test data met the measurement standards, reducing the problem of performance being affected by the use of discarded concrete blocks;

[0087] S5: Construction plan: formulate construction methods, including specific measures for mixing, transportation, pouring, vibration and maintenance;

[0088] S6: Quality control: Perform quality control during the construction process to ensure that the performance of the concrete meets the design requirements;

[0089] S7: Maintenance and evaluation: Proper maintenance should be carried out after concrete pouring, and the strength and performance of concrete should be evaluated regularly to ensure long-term stability, effectively reduce carbon emissions, save materials and reduce production costs overall.

[0090] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for designing low-strength oligomer concrete, comprising the following steps, characterized in that: S1: Determine the design requirements: clarify the strength grade of concrete, the use environment and the requirements for working performance; S2: Select materials: Select suitable curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials; S3: Mix design: Design the proportions of curing agent, coarse aggregate, iron tailings, water, water reducer and early strength agent according to the concrete strength requirements and working performance; S4: Testing and adjustment: Conduct concrete trial mix tests and optimize the mix ratio based on test data and standard methods; S5: Construction plan: formulate construction methods, including specific measures for mixing, transportation, pouring, vibration and maintenance; S6: Quality control: Perform quality control during the construction process to ensure that the performance of the concrete meets the design requirements; S7: Maintenance and evaluation: Proper maintenance should be carried out after concrete pouring, and the strength and performance of concrete should be evaluated regularly to ensure long-term stability, effectively reduce carbon emissions, save materials and reduce production costs overall.

2. The method for designing low-strength oligomer concrete according to claim 1, characterized in that: The curing agent, coarse aggregate, iron tailings, water, water reducing agent and early strength agent materials are mixed according to the proportions.

3. The method for designing oligomer low-strength concrete according to claim 1, characterized in that: The mass of the curing agent accounts for 1 of the total amount of concrete, the mass of the coarse aggregate accounts for 2.2-3.6 of the total amount of concrete, and the mass of the iron tailings accounts for 0.8-2.0 of the total amount of concrete.

4. The method for designing low-strength oligomer concrete according to claim 1, characterized in that: The mass of water accounts for 0.92 of the total amount of concrete, the mass of water reducing agent accounts for 0.01-0.015 of the total amount of concrete, and the mass of early strength agent accounts for 0.015 of the total amount of concrete.

5. The method for designing oligomer low-strength concrete according to claim 1, characterized in that: The concrete trial mix test observed and recorded the compressive strength and slump of the concrete at three, seven and twenty-eight days.

6. The method for designing oligomer low-strength concrete according to claim 1, characterized in that: After the concrete trial mix test, the fluidity, compressive strength, flexural strength and vertical expansion of the concrete are tested, and the mix ratio is optimized based on the test data and standard methods so that the overall test data meets the measurement standards.

7. The method for designing oligomer low-strength concrete according to claim 1, characterized in that: Through the synergistic effect of the material and steel slag, a composite concrete material with good working performance is prepared.

Citation Information

Patent Citations

  • Processing technology of concrete doped with waste concrete blocks

    CN111087188A

  • A concrete processing technology incorporating waste concrete blocks and the resulting recycled concrete

    CN112456880B

  • A method for preparing recycled concrete mixed with waste concrete blocks

    CN113117809B